Democracy - "Dunn, John" (New York, 2005)
For the last twenty-five years, fostering democracy around the world has been a cornerstone of U.S. foreign policy. Why is democracy so important today? Why should it hold such sway over the political speech of the modern world? In Democracy: A History , John Dunn – England's leading political theorist — sets out to explain the extraordinary presence of democracy in today's world. The story begins in Greece, where it began as an improvised remedy for a very local difficulty twenty–five hundred years ago. Athens gave democracy a name (demokratia) and worked out an elaborate, highly distinctive, and astonishingly thorough interpretation of the political conditions required to achieve it. However, democracy's tenure was short–lived, flourishing briefly and then fading away almost everywhere for nearly two thousand years. Democracy then suddenly reappeared with the founding of the new American republic and amid the struggles of France's Revolution. The word democrat suddenly became a partisan label and a badge of political honor, lending credibility to the idea of transforming human collective life, anywhere and everywhere, to fit the requirements of democracy that are so familiar to us today.
Keywords: Democracy-History